Real World Ecology Large-Scale and Long-Term Case Studies and Methods - Miao, ShiLi; Carstenn, Susan; Nungesser, Martha (Springer New York : Imprint: Springer, 2009)
Increasingly, ecosystem management and restoration efforts require understanding ecological processes that occur at large temporal and spatial scales. These phenomena are difficult to study using traditional statistical approaches that require randomization, replication, and control conditions. This book presents nine case studies highlighting new quantitative tools that scientists can apply to the design and analysis of large-scale, long-term experiments. Each case study identifies inherent constraints posed by traditional experimental tools and then suggests solutions that match appropriate novel experimental designs and analyses to the research questions. A conceptual framework has emerged from these studies relating spatial and temporal scales of scientific questions to methods, available data, and current knowledge about processes and mechanisms. This book provides invaluable guidance to ecologists who conceptualize, design, analyze, and synthesize real world ecological research.